POLYMERS WITH QUINOLINE FRAGMENTS (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Photochromic materials have potential applications for information storage, the controlled on/off digital switching of synthesized molecules by photo-irradiation. Therefore, our current research interests concern new polymer materials for photonics applications. We will focus on investigation of a new type of polymers with styrylquinoline fragment. Photochemical properties of such polymers can be advantageously addressed for photonics and nonlinear optics. In addition, the spatial organization of the active side chain residues along the polymeric backbone is of critical importance regarding mechanical and structural properties of the material. The principles of design of various molecular photoswitches and logicaldevices, in particular, those based on the photoisomerization reaction of diarylethylenes, have been actively investigated in recent years. The presence of additional functional groups in molecules of diarylethylenes, for example, crown ether groups, makes it possible to control the photochemical properties of diarylethylenes by the action on these groups. In styrylquinolines, the role of such a functional group is played by the endocyclic nitrogen atom, protonation of which changes the quantum yield of the trans–cis photoisomerization reaction. In the present paper we report the synthesis of side chain methacrylic polymers functionalized with styrylquinoline fragments. For the first time there have been synthesized and characterized methacrylic styrylquinoline containing monomers and polymers. Their structures have been confirmed by spectral methods. The polymerization ability of the new monomers was investigated kinetically for radical homopolymerization and copolymerization using dilatometric method in DMF solution with AIBN as radical initiator (argon atmosphere). Polymers were characterized, as well as the glass transition temperatures(Tg) and molecular weights were determined.
Keywords: quinolines; methacrylates; styrylquinoline polymers